2005
DOI: 10.1093/cs/27.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Bullying in School: An Overview of Types, Effects, Family Characteristics, and Intervention Strategies

Abstract: Bullying represents a significant problem in U.S. schools, affecting approximately one in three children. The authors discuss the dynamics, types, characteristics, and consequences of school bullying. Risk factors for engaging in bullying, being bullied, and becoming both a bully and a victim are discussed. Research indicates that bullying has serious long-term negative effects on bullies, victims, and victims who tum to bullying as a coping strategy. Longitudinal relationships between childhood bullying and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
270
0
37

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 368 publications
(331 citation statements)
references
References 26 publications
8
270
0
37
Order By: Relevance
“…According to Smokowski and Kopasz (2005), bullying is the most ubiquitous type of youth violence. Project staff work collaboratively with school counselors and social workers to solve bullying-related issues.…”
Section: Educationmentioning
confidence: 99%
“…According to Smokowski and Kopasz (2005), bullying is the most ubiquitous type of youth violence. Project staff work collaboratively with school counselors and social workers to solve bullying-related issues.…”
Section: Educationmentioning
confidence: 99%
“…Previous studies have shown that bullying behaviour has a detrimental effect on both victims and offenders (2). It was associated with negative outcomes such as psychological maladjustment (psychological well-being, self-esteem, and self-confidence) (3,(5)(6)(7)(8), psychosomatic health problems (9), and involvement in substance use and other risk behaviours (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…To date, much research on the relationship between teachers and classroom bullying has largely centered on teachers' classroom management, with a specific emphasis on discipline practices within the classroom (Bullock 2002;Smokowski and Kopasz 2005). Advocates of a classroom management approach to ameliorating bullying argue that "teachers who are adept at managing student behavior in the classroom work to prevent student bullying through creating a classroom climate incompatible with peer victimization… work to improve children's social skills and conflict management skills so that future bullying is less likely" (Crothers and Kolbert 2010, p. 537).…”
Section: Introductionmentioning
confidence: 99%